Issues of Blended Translation Teaching in Higher Education: a Systematic Literature Review (SLR) - Retnomurti, Ayu Bandu; Rasyid, Yumna; Dewanti, Ratna (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2024)
Blended teaching is prevailing among universities. This teaching mode can improve translation training effectiveness and facilitate the construction of translation discipline. As far as the translation field is concerned, the lack of translation technical resources and their inappropriate application are at the forefront. In response to these problems, this research aims on a systematic literature review: to clarify the concept of